Energy potential of waste from Brazil nut (Bertholletia excelsa H.B.K.) for production of activated carbon (Research, Society and Development, 2021)
To choose the most efficient energy generation process, it is necessary to know the properties chemical and thermal effects of biomass. The shells and hedgehogs of Brazil nut (Bertholletia excelsa H.B.K.), generally treated as waste, they have aroused the interest of researchers in the energy sector due to their fuel properties. This work aims to evaluate the energetic properties of seed shells and hedgehogs Brazil nut to use them in the production of adsorbents. The physical-chemical and thermal tests of the biomasses were investigated by the techniques of Proximate Analysis (moisture, ash, volatiles and fixed carbon), Ultimate Analysis, High Heating Value (HHV), Lower Heating Value (LHV) and Thermogravimetry (TG/DTG). The adsorbents, CA-1 (shells) and CA-2 (hedgehog), were produced by chemical activation with ZnCl2 followed by carbonization at 500ºC for 90 min. The results of the characterization for the biomasses showed moisture between 8-9%, ash below 2.8%, and high volatiles (85%) LHV and HHV nearby, in the range between 15-17 MJ/kg. The yield of the process of obtaining activated carbon (~74%) was higher than the literature. The evaluation of the adsorbents regarding the methylene blue adsorption process proved to be efficient, activated carbon produced from the shells showed a greater adsorptive capacity when compared to the adsorbent produced from hedgehogs. Finally, the biomasses demonstrated a good energy potential and as an alternative to commercial activated carbon, promoting the use of waste and contributing as a possible solution in the search for low-cost precursor materials for adsorbents production.